2020
DOI: 10.1111/obr.12986
|View full text |Cite
|
Sign up to set email alerts
|

Rising prevalence of BMI ≥40 kg/m2: A high‐demand epidemic needing better documentation

Abstract: Summary Whilst previously rare, some surveys indicate substantial increases in the population with body mass index (BMI) ≥40 kg/m2 since the 1980s. Clinicians report emerging care challenges for this population, often with high resource demands. Accurate prevalence data, gathered using reliable methods, are needed to inform health care practice, planning, and research. We searched digitally for English language sources with measured prevalence data on adult BMI ≥40 collected since 2010. The search strategy inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 76 publications
1
35
0
1
Order By: Relevance
“…While other studies have demonstrated that differentiating females with ADHD in comparison to other patient groups with the CAARS was difficult 19 , we achieved such differentiation successfully in this study. The prevalence rates of obesity for men and women in Germany are similar 23 , though concerning morbid obesity (BMI ≥ 40 kg/m 2 ), females’ rates (2.8%) are more than twice that of males (1.2%) in Germany according to a recent meta-analysis 24 , and our data. More females were enrolled in our control group, as is usually the case in voluntary studies 25 like ours.…”
Section: Discussionsupporting
confidence: 71%
“…While other studies have demonstrated that differentiating females with ADHD in comparison to other patient groups with the CAARS was difficult 19 , we achieved such differentiation successfully in this study. The prevalence rates of obesity for men and women in Germany are similar 23 , though concerning morbid obesity (BMI ≥ 40 kg/m 2 ), females’ rates (2.8%) are more than twice that of males (1.2%) in Germany according to a recent meta-analysis 24 , and our data. More females were enrolled in our control group, as is usually the case in voluntary studies 25 like ours.…”
Section: Discussionsupporting
confidence: 71%
“…A limitation of this study was the relatively small number of participants and the time of follow-up. Despite the still-rising percentage of people suffering from morbid obesity (BMI of ≥40 kg/m 2 ) in Poland, compared to that in other countries, this percentage is still fairly small (only 1.3% of men and 1.8% of women) [37]. Another limitation was the relatively small number of patients in whom the LRYGB was performed, which made it difficult to compare the results of the surgery methods.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of severe obesity (BMI ‡35 kg/m 2 ) is rising at an alarming pace; by 2030, it is projected to affect one in four adults. 191,192 Considering that conventional weight-loss interventions (diet, exercise, drugs) have minimal impact in patients with severe obesity, 193 it is particularly noteworthy that long-term TTh for up to 8 years reduced BMI from 37.3 to 29.5 in men with grade II obesity (BMI 35-39.9) and from 41.9 to 32.4 in men with grade III obesity. 55 This suggests that TTh also offers significant clinical value for men with more severe obesity.…”
Section: Discussionmentioning
confidence: 99%